Differences in Characteristics and Ambulance Pathway Adherence Between Strokes and Mimics Presenting to a Large UK Centralized Hyper Acute Stroke Unit (HASU) - Sammut-Powell, Camilla; Ashton, Christopher; Paroutoglou, Kyriaki; Parry-Jones, Adrian (Frontiers in Neurology, 2021)
Background: In Greater Manchester (GM), prehospital clinicians use the Face Arm Speech Timest (FAST) test (FAST) to identify suspected stroke patients alongside pathway exclusions. Within the centralized stroke service, patients with a suspected stroke are taken directly to a Hyper Acute Stroke Unit (HASU), often bypassing their local emergency department (ED). However, many of these patients are experiencing something an illness that looks like a stroke but is not a stroke. The data collected in the prehospital setting is rarely used in research yet could give valuable insights into the performance of the pathway. Aim: To evaluate the presenting symptoms and final diagnoses of patients that were prehospital suspected strokes of having stroke in the prehospital setting and to evaluate the adherence of prehospital stroke pathway exclusions and how often these were correctly overruled. Methods: We analyzed data from all patients brought in by ambulance and admitted on the stroke pathway between 01/09/15 and 28/02/17. Patient demographics and all data recorded in the prehospital setting were evaluated to identify differences in stroke, TIA and mimic patients., and p Pathway adherence was assessed according to whether the patient was local or out-of-area (OOA) and bypassed their local ED. Results: A total of 4216 suspected strokes were identified: 2213 (52.5%) had a final diagnosis of stroke, 492 (11.7%) experienced a transient ischemic attack (TIA) and 1511 (35.8%) were stroke mimics. There were 714 (16.9%) patients that were identified as having at least one pathway exclusion or were FAST negative, of which 270 (37.8%) experienced a stroke. The proportion of strokes was significantly lower in those with a pathway exclusion (41.8% vs 53.5%; p<0.001) and the proportion of breaches tended to be comparable or higher in the local population. Discussion: There are high volumes of stroke mimics but identified differences indicate there is an opportunity to better utilize prehospital data. Ambulance clinicians were able to correctly overrule FAST negative results and the volume of these suggest that , and FAST alone may be too restrictive.